Building condensation How to solve the problem in Portugal - V. P. de FREITAS (2002)
Humidity is one of the major causes of problems with residential buildings. Condensation on the inner surface of buildings envelope is one of the ways humidity appears, with this phenomenon affecting thousands of homes built recently in Portugal. It is important to reflect upon the causes that lie behind condensation and to define a set of regulations to be complied with by the construction industry, in order to solve the problem, as we take into consideration the actual conditions in which the buildings are used. This paper seeks to analyse the physical phenomenon that lies behind condensation, order the causes in a hierarchical fashion, reflect on hygrothermal conditions within buildings and offer solutions for solving the problem.